MRT station and urban linkage at khamabari-Indira road-Farmgate - Muttaqi, Nur-e-Dipha Shamima (BRAC University, 2012)
This thesis is submitted in partial fulfillment of the requirements for the degree of Bachelor of Architecture in Architecture, 2012.